The Jonas Hypertension Program: An Academic–Community Partnership to Address Hypertension in Four Dominican Bateyes. (March 2019) - Conley, Tammie; Enriquez, Maithe; Cheng, An-Lin; Jorge, Dorcas; Meristal, Sandy Yan; Coe, Benjamin; Logan, Pamela R.; Stiles, Steven; Beall, Ginny; Biggs, Alfred; McKinsey, David S.
Introduction: Adults living in bateyes (i.e., sugarcane plantation villages) in the Dominican Republic have minimal access to health care services. Hypertension (HTN) is a serious and often unrecognized health problem among batey residents. The Jonas Batey Hypertension Program was built on existing social networks to address the detection and treatment of HTN. Methods: An ongoing community-based participatory research endeavor involves a partnership among three organizations and collaboration with promotoras who engage their batey communities in a mobile HTN screening and treatment program. Adults are screened and, if indicated, are treated with antihypertensive medications. Data collection includes project documentation, participant observation, demographic data, blood pressure (BP) measurements, and pill counts. Results: To date, 243 adults have received HTN treatment in four batey communities. A within-group, as-treated, repeated-measures, pre-/postanalysis showed that among participants who had been receiving antihypertensive treatment for 12 months ( n = 70), there was a significant decrease in BP ( p < .005). Conclusion: Results of an interim data analysis indicate that the program model has been implemented successfully and is making a positive impact on BP control. Evaluation is ongoing with regard to the long-term HTN-related health outcomes of batey residents. Ensuring program sustainability is an important consideration for the future.